How do you solve: square root of (x+6)=x

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

How do you solve: square root of (x+6)=x

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

x=3 and x=-2
just square both sides, and you will get a quadratic equation, then factor it out.
square root (x+6) = x Square both sides x+6 = x^2 x^2-x-6 = 0 (x-3)(x+2) = 0 x-3 = 0 x = 3 x+2 = 0 x = -2 Even though x=3 and x=-2 the only solution is x=3 because of the following: square root (3+6) = 3 Square root 9 = 3 which is a true statement square root (-2+6) = square root 4 = 2 but the second solution states that x=-2 and therefore the square root 4 does not equal -2

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

-2 is a extraneous root
it is an extraneous root

Not the answer you are looking for?

Search for more explanations.

Ask your own question